2021
DOI: 10.7717/peerj.11909
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-L-tryptophan attenuates hepatic ischemia-reperfusion injury via regulating TLR4/NLRP3 signaling pathway in rats

Abstract: The aim of this study was to investigate the changes of TLR4/NLRP3 signal during hepatic ischemia-reperfusion injury (HIRI) and to verify whether N-acetyl-L-tryptophan (L-NAT) protected hepatocytes by regulating the activation of TLR4/NLRP3 signal. We have established the rat HIRI model and H2O2-induced cell damage model to simulate ischemia-reperfusion injury and detect the corresponding indicators. Compared with the sham group, Suzuki score and the level of serum ALT increased after HIRI, accompanied by an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…A study conducted by Li et al suggested that DHA alleviates hepatic I/R injury by activating the PI3K/Akt pathway and subsequently inhibiting the canonical pyroptotic pathway [ 104 ]. Similarly, N-acetyl-1-tryptophan can lighten hepatic I/R injury via inhibiting the TLR4/NLRP3/caspase-1 signaling pathway [ 105 ]. Moreover, hepatic I/R injury was attenuated in caspase-1/caspase-11 double-gene knockout mice, suggesting that apart from the canonical pyroptotic pathway, the non-canonical pathway of pyroptosis is also involved in liver I/R injury [ 106 ].…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%
“…A study conducted by Li et al suggested that DHA alleviates hepatic I/R injury by activating the PI3K/Akt pathway and subsequently inhibiting the canonical pyroptotic pathway [ 104 ]. Similarly, N-acetyl-1-tryptophan can lighten hepatic I/R injury via inhibiting the TLR4/NLRP3/caspase-1 signaling pathway [ 105 ]. Moreover, hepatic I/R injury was attenuated in caspase-1/caspase-11 double-gene knockout mice, suggesting that apart from the canonical pyroptotic pathway, the non-canonical pathway of pyroptosis is also involved in liver I/R injury [ 106 ].…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%
“…As the most studied tissue-damage detector, the NLR family pyrin domain-containing 3 (NLRP3) inflammasome is composed of NLRP3, apoptosis-associated speck-like protein (ASC) and caspase-1, which is prominent in initiating and propagating the inflammatory responses 12 . Previous evidence suggests that the NF-κB signaling leads to NLRP3 activation that participates in the pathogenesis of hepatic IRI 13 . Thus, the TLR-4/NF-κB/NLRP3 inflammatory pathway might be involved in hepatic IRI.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of experimental studies have indicated that ischemia/reperfusion-induced liver injury occurs in a biphasic manner [15]. Data obtained by several different research groups suggest that in both early and late phases of reperfusion injury, oxidative stress is one of the main pathogenic mechanisms [20,24,30,31],. SOD and GSH-Px are important antioxidants, and MDA is a product of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%